?PREPARATION AND CHARACTERISATION OF MIXED LIGAND COMPLEXES OF Co(III), Fe(III), and Cr(III) CONTAINING PHTHALIMIDE AND PHENOLS (Biological Sciences - PJSIR, 1996)
Some novel mixed ligand complexes of Co(III), Fe(III) and Cr(lll) containing phthalimide as primary and 2- aminophenol and 3-aminophenol as secondary Jigands have been synthesised and characterised on the basis of elemental analyses, conductivity and magnetic measurements and infrared and electronic spectral studies. Com- plexes containing 2-aminophenol are 1 : 1 electrolyte in N,N dimethylformamide. Spectral studies indicate that all the complexes exhibit octahedral geometry.The complexes have the general composition: K[M(pim)/L)2]; where M=Co(III), Fe(III) and Cr(III), pimeanion of phthalimide and Leanion of 2-arninophenol and 3-aminophenoL